Harmonic progressions of hindi songs based on North Indian Ragas - Ruwin Rangeeth Dias, Wajjakkara Kankanamalage (2015)
Hindi film music directors have been composing raga based Hindi film songs applying harmonic progressions as experienced through various contacts with western music. This beginning of hybridization reached different levels in the past nine decades in which Hindi films were produced. Early Hindi film music used mostly musical genres of urban theatre traditions due to the fact that many musicians and music directors came to the early film music industry from urban theatre companies. Their music education included to a great part western music transmitted through colonial formal education. Moreover, Hindi film music directors use unique methods apart from average western harmonization while blending North Indian ragas with harmonic progressions. The pre-electronic music production period is in this regard the most interesting since in this time period many compositions were successively elaborated by learning film music composers. Special attention is, therefore, given to the time between the 1960s and 1970s. There is a sufficient amount of samples to choose from composed by Hindi film music directors, who composed raga based Hindi film songs that they were hybridizing with harmonic progressions. However, this ‘learning’ period paved the way for further applications of harmonic progressions in Hindi film music generally and deserves therefore a close look in order to understand current developments. Three composers and composer duos selected show remarkable differences in their approaches and seem to represent the diversity of raga based film songs with harmonic progressions. The selected Hindi film music directors are the composer duo Shankar and Jaikishan, the composer Rahul Dev Burman, and the composer duo Laxmikant and Pyarelal. Musical analysis is conducted using spectral analysis, simplified analysis of harmonic progressions, and a thorough raga analysis. Personal communications with music directors and related literature are elaborated to support the analysis. This study is to answer the question: how and why North Indian ragas are hybridized with Western harmonic progressions in Hindi film songs. This question is followed by sub questions: Did Hindi film music directors apply harmonic progressions on a raga based Hindi film song purposely or by chance? If they applied harmonic progressions purposely, is it to increase the attractiveness of the song, or did they just make use of their educational advantages? How other music composers’ creations influenced Hindi film music directors and how are music directors perceived by the audience? How diverse and how complex are harmonic progressions used in Hindi film songs? How are different ragas linked in Hindi film songs using harmonic progressions? Are there any possibilities to shift tonics in ragas through harmonic progressions, which may definitely modify the perception of ragas? These questions are discussed in this study. This study is to stimulate discussion on the understanding of hybridization methods used in the pre electronic era of Hindi film songs and to lead to a higher awareness of current developments in Hindi film music, including the phenomenon of its high popularity in cultural exchange with cultures outside India. Methodically, this study allows analyzing Hindi film songs in a broader sense to scrutinize North Indian ragas and harmonic progressions in their immediate cultural environment. It is important to the community of present musicians that are interested in hybridizing music of diverse cultural origin.